(untitled) (Journal of Informatics Education and Research, 2025)
Artificial Intelligence (AI) within journalism has dramatically changed news production, editing, and dissemination worldwide. With the emergence of automation and algorithmic content generation, AI has brought about new efficiencies and issues in the media environment. In India, TV remains among the most powerful media for mass communication. Hence, it is important to know how TV journalists view and work with AI technologies as part of their professional work. The present research paper examines the degree of awareness and the level of AI deployment among Indian television journalists, explicitly focusing on the use of Robotic Journalism in news production. Using a standardized questionnaire sent out to reporters in top national news networks, the research focuses on their awareness of AI principles, particular tools, and usage frequency within regular working patterns. The conclusions drawn in this research endeavour to gauge the readiness of Indian newsrooms to face AI-led transformation and determine the prevailing gaps in knowledge, skill, or infrastructure that can hinder the seamless adoption of AI technologies in the television news industry.